Implementation of Al-Qur'an Hadith Learning Based on Brainstorming Methods - Nisa', khoirun; Wahyudi; Ikhlima Qurrotu Izza Rizqiyyah; Trianawati, Anis (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study aims to describe the application of the Brainstorming method to student creativity using a qualitative approach. This research is qualitative research. Data collection uses observation, interview, and documentation techniques. The results of the research show that the Brainstorming learning method on the Al-Qur'an Hadith subject at Islamic Elementary School Walisongo Sumberrejo Pasuruan has been implemented since 2023. In its implementation, there are advantages and disadvantages, but with this method, students become active and enthusiastic in learning so it can be concluded that the Brainstorming method is very appropriate if implemented in schools so that learning is more effective and makes students not bored in learning.